Personal continuity of care in a university-based primary care practice: impact on blood pressure control - Hanafi, Nik Sherina Haidi; Abdullah, Adina; Lee, Ping Yein; Liew, Su May; Chia, Yook Chin; Khoo, Ee Ming (Public Library of Science, 2015)
Continuity of care is an important quality outcome of patient care. This study aimed to investigate the relationship between personal continuity and blood pressure (BP) control among the patients with hypertension in an academic primary care centre. Between January and May 2012, we conducted a retrospective review of medical records of patients with hypertension who had been followed up for at least 1 year in the Primary Care Clinic, University of Malaya Medical Centre, Malaysia. In this setting, doctors who provided care for hypertension included postgraduate family medicine trainees, non-trainee doctors and academic staff. Systematic random sampling (1:4) was used for patient selection. BP control was defined as less than 130/80 mm Hg for patients with diabetes mellitus, proteinuria and chronic kidney disease and less than 140/90 mm Hg for all other patients. Continuity of care was assessed using the usual provider continuity index (UPCI), which is the ratio of patient visits to the usual provider to the total number of visits to all providers in 1 year. A UPC index of zero denotes no continuity while an index of one reflects perfect continuity with only the usual provider. We reviewed a total of 1060 medical records. The patients’ mean age was 62.0 years (SD 10.4). The majority was women (59.2%) and married (85.7%). The mean number of visits in a year was 3.85 (SD 1.36). A total of 72 doctors had provided consultations (55 postgraduate family medicine trainees, 8 non-trainee doctors and 9 academic staff). The mean UPCI was 0.43 (SD 0.34). Target BP was achieved in 42% of the patients. There was no significant relationship between BP control and personal continuity after adjustment for total number of visits. Continuity of care was not associated with BP control in our centre. Further studies are needed to explore the reasons for this.